2016
DOI: 10.1111/bjep.12136
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic testing and test anxiety amongst gifted and average‐ability children

Abstract: Dynamic testing proved to be successful in improving the scores of the children, although no differences in training benefits were found between gifted and average-ability children. Test anxiety was shown to influence the children's rate of change across all test sessions and their improvement in performance accuracy after dynamic training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
11
0
3
Order By: Relevance
“…De acuerdo con ello, algunas acciones desarrolladas con el alumnado de esta etapa concluyen la eficacia de las intervenciones cognitivo-conductuales de carácter breve (Yeo, Goh y Liem, 2016), así como aquellas basadas en la relajación a través de la respiración profunda (Khng, 2017). Asimismo, se ha sugerido la conveniencia de reemplazar los tradicionales exámenes, basados en medir el aprendizaje previo del alumnado, por pruebas de carácter dinámico, focalizados en evaluar el potencial para el aprendizaje (Vogelaar, Bakker, Elliott, y Resing, 2017). En aras de fomentar específicamente la autoestima del estudiantado, se ha sugerido que el profesorado (Boehme et al, 2017;Lohbeck et al, 2016): (a) proporcione una retroalimentación frecuente e individualizada; (b) proponga tareas adaptadas al nivel competencial de su alumnado; (c) promueva el aprendizaje colaborativo; (d) evite la comparación social; y (e) estimule las creencias de control del estudiantado (e.g., fomentar su autonomía, establecer con claridad los objetivos de las tareas y las estrategias eficaces para llevarlas a cabo).…”
Section: Discussionunclassified
“…De acuerdo con ello, algunas acciones desarrolladas con el alumnado de esta etapa concluyen la eficacia de las intervenciones cognitivo-conductuales de carácter breve (Yeo, Goh y Liem, 2016), así como aquellas basadas en la relajación a través de la respiración profunda (Khng, 2017). Asimismo, se ha sugerido la conveniencia de reemplazar los tradicionales exámenes, basados en medir el aprendizaje previo del alumnado, por pruebas de carácter dinámico, focalizados en evaluar el potencial para el aprendizaje (Vogelaar, Bakker, Elliott, y Resing, 2017). En aras de fomentar específicamente la autoestima del estudiantado, se ha sugerido que el profesorado (Boehme et al, 2017;Lohbeck et al, 2016): (a) proporcione una retroalimentación frecuente e individualizada; (b) proponga tareas adaptadas al nivel competencial de su alumnado; (c) promueva el aprendizaje colaborativo; (d) evite la comparación social; y (e) estimule las creencias de control del estudiantado (e.g., fomentar su autonomía, establecer con claridad los objetivos de las tareas y las estrategias eficaces para llevarlas a cabo).…”
Section: Discussionunclassified
“…In conclusion, high intelligence does not always reflect faster performance (Reams, Chamrad & Robinson, 1990). In the same vein, some studies have shown an equivalent learning progression in intellectually gifted and average children (Vogelaar, Bakker, Elliott, & Resing, 2017a;2017b;Vogelaar, Resing, Stad, & Sweijen, 2019). Although there are some contradictory results (Calero, Belen, & Robles, 2011;Kanevsky & Geake, 2004), the rapidity to learn in IGC seems not to distinguish from IAC in the potential of learning.…”
Section: Attentional Network In Gifted Children !mentioning
confidence: 99%
“…Although there are some contradictory results (Calero, Belen, & Robles, 2011;Kanevsky & Geake, 2004), the rapidity to learn in IGC seems not to distinguish from IAC in the potential of learning. The specificity of intellectual giftedness concerns on the high capacity to learn and to generalize their newly acquired knowledge in other contexts (Calero et al, 2011;Vogelaar et al, 2017aVogelaar et al, , 2017bVogelaar et al, , 2019. This high learning capacity might be tied to their high performance in reasoning (Caropreso & White, 1994), working memory (Calero, García-Martín, Jiménez, Kazén, & Araque, 2007;Hoard, Geary, Byrd-Craven, & Nugent, 2008;Leikin, Paz-Baruch, & Leikin, 2013;van Viersen, Kroesbergen, Slot, & de Bree, 2014), metacognitive abilities (Oppong, Shore, Muis, 2019) and executive functions (Arffa, 2007).…”
Section: Attentional Network In Gifted Children !mentioning
confidence: 99%
“…A primeira é uma emoção transitória, provocada por uma situação específica, enquanto que a segunda é uma inclinação ou disposição crônica, que emerge como estado numa grande variedade de situações. Nos contextos de aprendizagem escolar, têm sido identificadas, como particularmente frequentes, ansiedade em ralação à matemática e ansiedade nas situações de prova (por ex., BZUNECK, 1991;CASSADY;JOHNSON, 2002;ERTURAN;JANSEN, 2015;JUSTICIA-GALIANO et al, 2016;VOGELAAR et al, 2017). A ansiedade de prova seria uma expressão da ansiedade-traço, porém, com possível influência adicional de outros fatores, como o contexto da prova, a percepção de ameaça, a autopercepção de competência, padrões pessoais de enfrentamento e de motivação e até habilidades de estudo (ZEIDNER, 2014).…”
Section: O Impacto Das Emoções No Contexto Escolarunclassified